Prognostic significance of Cyclooxygenase-2 expression in colorectal adenoma and Adenocarcinoma: A clinicopathologic study - Noor I. Ibrahim; Shazana H. Shamsudin; Suk K. Lee; Sharifah Emilia T. Sharif (Elsevier, 2023)
Background: A new prognostic biomarker for colorectal cancer (CRC) is imperative and cyclooxygenase-2 (COX-2) has the potential as a new candidate. We aimed to investigate the differential expression of COX-2 and its relationship with clinicopathological features of colorectal neoplasms. Methods: We retrospectively investigate 91 cases of colorectal adenoma and 215 cases of adenocarcinoma by immunohistochemical assessment of COX-2 expression in the neoplastic epithelial and stromal cells. The differential COX-2 expression and its association with clinicopathological features was statistically evaluated. Results: Significantly high expression of COX-2 was observed in the cytoplasm of the epithelial cells of adenocarcinoma (66.0 %) and stromal cells of adenoma (50.5 %), whilst low expression was seen in the stromal cells of adenocarcinoma (5.1 %) and epithelial cells of adenoma (26.4 %), (P < 0.0005). The epithelial COX-2 overexpression of adenocarcinoma was significantly associated with moderate differentiation (p = 0.030), usual-type histology (p = 0.049), deeper invasion (p = 0.007), higher Astler Coller stage (p = 0.009), positive nodal metastasis (p = 0.011) and lymphovascular invasion (p = 0.005). In adenoma, high epithelial COX-2 expression showed significant association with advanced age (p = 0.008) and smaller adenoma (p = 0.034), while stromal COX-2 overexpression was significantly associated with low-grade dysplasia (p = 0.003). In the tumor microenvironment, COX-2 expression was observed mainly in the inflammatory cells, with weaker expression seen in the fibroblasts and vascular endothelial cells. Conclusion: COX-2 overexpression is significantly associated with favorable characteristics of colorectal adenoma and advanced features of colorectal adenocarcinoma, thus portraying its potential as a prognostic biomarker for CRC detection.